2008
DOI: 10.1039/b802562b
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to the staggered herringbone mixer

Abstract: An analytical model of mixing in the staggered herringbone mixer (SHM) was derived to estimate mixing parameters and provide practical expressions to guide mixer design and operation for a wide range of possible solutes and flow conditions. Mixing in microfluidic systems has historically been characterized by the mixing of a specific solute system or by the redistribution of flow streams; this approach does not give any insight into the ideal operational parameters of the mixer with an arbitrary real system. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 35 publications
4
119
0
Order By: Relevance
“…The stucture still works as a mixer, but the degree of mixing becomes more unpredictable. For the staggered herringbone mixers, which also relies on grooves on the channel bed to rotate the flow field, it has been reported that at high Reynolds numbers (>10) vortices form in the grooves which significantly reduces the rotation (Williams et al 2008). Similar effects are also seen for three dimensional mixers working by the split and recombine principle, for example, good lamination is only observed with the caterpillar mixers for low Reynolds numbers (<30, (Schonfeld et al 2004)).…”
Section: 1supporting
confidence: 50%
“…The stucture still works as a mixer, but the degree of mixing becomes more unpredictable. For the staggered herringbone mixers, which also relies on grooves on the channel bed to rotate the flow field, it has been reported that at high Reynolds numbers (>10) vortices form in the grooves which significantly reduces the rotation (Williams et al 2008). Similar effects are also seen for three dimensional mixers working by the split and recombine principle, for example, good lamination is only observed with the caterpillar mixers for low Reynolds numbers (<30, (Schonfeld et al 2004)).…”
Section: 1supporting
confidence: 50%
“…Kee and Gavriilidis [21] numerically evaluated mixing performance of the SHM at Re = 0.001 − 10, in which 3-D velocity field was obtained via COMSOL simulations, and particle tracking methods were used to quantify the mixing performance to avoid numerical diffusion problems. Recently, Williams and colleagues [22] used confocal microscopy and COMSOL modeling to develop and evaluate analytical models of mixing in the SHM. They concluded that mixing was only a function of Péclet number and downstream position in the mixer.…”
Section: Open Accessmentioning
confidence: 99%
“…To characterize the mixing performance of the micromixers in order to better understand and design more efficient micromixers for different applications, a number of techniques, both experimentally [14][15][16][17][18] and theoretically [12,[19][20][21][22][23][24][25][26][27][28], have been employed. Particularly, CFD has been widely used to study the mixing behavior of micromixers in details.…”
Section: Open Accessmentioning
confidence: 99%
“…The herringbone mixing structure [32][33][34] was chosen as static mixer as it was found to be efficient at low Reynolds numbers. In the experiments described in the present study, the Reynolds number were estimated to be in the range of Re≈20.…”
Section: Densitymentioning
confidence: 99%